AGING ATTITUDES AND TELEVISION WATCHING: IMPLICATIONS FOR WELL-BEING - Giasson, H.L. (Innov Aging, 2017)
Television can be an exciting escape, or a self-handicapping behavior adversely linked to health and well-being. We examine associations between individuals’ television watching and their attitudes toward their own aging using data from the Health and Retirement Study (N=5542). Analyses revealed that positive aging attitudes like “as I get older, things are better than I expected” were associated with fewer hours spent watching television, whereas negative attitudes like “the older I get, the more useless I feel” were associated with a greater number of hours spent watching television. Additionally, positive aging attitudes were associated with higher positive affect while watching TV. Negative aging attitudes were associated with lower positive affect and higher negative affect while watching TV. All analyses controlled for gender, race, age, education, work status, depressive symptoms, functional limitations, day of week, and trait positive and negative affect. We discuss possible cognitive, affective, and behavioral mechanisms.